1998
DOI: 10.1098/rsta.1998.0203
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial tension effects on slag—metal reactions

Abstract: Dynamic X-ray imaging of a metal droplet in a slag phase is an elegant way to monitor the rate of the interfacial reactions. In an attempt to follow the kinetics of dephosphorization, the changes in the shape of the sessile drop of molten iron with 0.1 wt% P immersed in a slag kept in MgO crucibles were recorded as a function of time. The slag had an initial composition 40 wt% CaO, 30 wt% SiO 2 and 30 wt% Fe 2 O 3 . While in a set of runs, solid iron was added to the molten slag, the sequence was reversed in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 3 publications
1
22
0
Order By: Relevance
“…[1][2][3][4][5] Interfacial phenomena studies mainly focusing on Marangoni forces and interfacial tensions have also been dealt with extensively. [6][7][8][9][10] The potential drive for this extensive research is the importance of interfacial reactions in metallurgical process occurring during metal refining, degasification process, and slag entrapment. However, some issues with respect to the interfacial properties need to be addressed, viz.…”
Section: Numerous Investigations Have Been Carried Outmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Interfacial phenomena studies mainly focusing on Marangoni forces and interfacial tensions have also been dealt with extensively. [6][7][8][9][10] The potential drive for this extensive research is the importance of interfacial reactions in metallurgical process occurring during metal refining, degasification process, and slag entrapment. However, some issues with respect to the interfacial properties need to be addressed, viz.…”
Section: Numerous Investigations Have Been Carried Outmentioning
confidence: 99%
“…The furnace had also been calibrated earlier with other metals like copper, nickel and iron [8] Cu : r Nm…”
Section: A Calibrationmentioning
confidence: 99%
“…The surface tension of the alloy was measured in a flow of purified inert gas by the sessile-drop method. Two different techniques were applied: the X-ray sessile-drop [5] and the large-pinned drop [7]. The experiments were performed from the liquidus temperature and above: the CMSX-4 liquidus temperature is T l = 1654.5 ± 4 K [11].…”
Section: Surface Tensionmentioning
confidence: 99%
“…The measurement of the density was performed by a levitation diffusivity technique, while that of the viscosity with an oscillating cup viscosimeter. The present study was carried out based on the technique and knowledge acquired from the previous experiments [5][6][7]. CMSX-4 is a nickel-based superalloy widely used in the aerospace industry for turbine blades.…”
Section: Introductionmentioning
confidence: 99%
“…[6] The phenomena also occur in systems other than liquid iron/ steel and slag. Some investigators reported the phenomena in reactions between liquid copper and molten Na 2 CO 3 [8] or during reactions between Cu-Ni-Al alloy with Li 2 O-Al 2 O 3 -SiO 2 slag. [9] The phenomena described are well observed and recognized; however, they are not fully understood.…”
Section: Introductionmentioning
confidence: 99%